Business, society and global governance a skills approach - Ni, Anna Ya; Van Wart, Montgomery 1951- (Routledge, 2023)
Business, Society and Global Governance is a comprehensive read for both upper-and lower-division undergraduate business or general education students. It offers the reader a thorough understanding of government's roles with business and the skills necessary to create and maintain successful relations with government. At the same time, it defines the roles business can play with government that are compatible with its own needs to achieve corporate objectives and fulfil corporate responsibilities. Business and governments need to operate in global contexts, and so the text concludes with several chapter regarding a variety of global business and governance structures. In this new edition the role of the nonprofit sector is also highlighted. It takes on a practical approach which integrates the political, economic, and social theories with business and government practices whilst allowing for an interdisciplinary perspective and opportunities for skill-building. This text also offers key learning resources, including key terms, cases studies, study questions and chapter summaries, which result in an accessible and supportive textbook for those looking to learn more about business-government relations in a societal context"--